NOVEL 4-FERROCENYL-8-(PHENYLTHIO)-1,2,3,4-TETRAHYDROQUINOLINE: DESIGN, SYNTHESIS AND SPECTRAL CHARACTERIZATION - Minić, Aleksandra; Bugarinović, Jovana; Pešić, Marko; Ilić Komatina, Danijela (Bulletin of Natural Sciences Research, 2019)
Herein, we report design, synthesis and spectral characterization of novel 4-ferrocenyl-8-(phenylthio)-1,2,3,4-tetrahydroquinoline. Desired synthesis was achieved in three reaction steps, with a good overall yield (67%). First step included aza-Michael addition of 2-(phenylthio)aniline to 1-ferrocenylpropenone, subsequently, the obtained ketone was smoothly reduced to the corresponding 1,3-amino alcohol. The final step was an intramolecular cyclization prompted by acetic acid, proceeding via corresponding α-ferrocenyl carbocation. The synthesized compounds have been isolated pure, and their structure have been undoubtedly confirmed by standard spectral techniques (1H NMR, 13C NMR, IR and elemental analyses).